Integrative taxonomy reveals first country record of Hyalinobatrachium mondolfii Señaris and Ayarzagüena 2001, and distribution range extensions for Cochranella nola Harvey 1996, and Rulyrana spiculata Duellman 1976 (Anura: Centrolenidae) in Peru - Chávez, Germán; Pradel, Renzo; Catenazzi, Alessandro (Zootaxa, 2019)
We used an integrative taxonomy approach to investigate the taxonomic identity of several populations of glassfrogs from Peru, which are notoriously challenging to identify due to their overall similarity in morphology and coloration. We relied on comparisons of morphology, bioacoustics, and partial fragments of 16S rRNA DNA sequences. We report for the first time the presence of Hyalinobatrachium mondolfii in Peru, being this the southernmost locality known for the species. Likewise, we update and extend the distribution ranges of Rulyrana spiculata and Cochranella nola in the Andes of Peru, provide a 16S sequence of a topotype of R. spiculata, and confirm its presence in Bolivia. For all three species, we increase the current knowledge on their geographic distribution and genetic and phenotypic variation.